Adaptación del Cuestionario para Identificación de Trastornos Debidos al Consumo de Alcohol (AUDIT) en universitarios colombianos. - Riveros, Fernando; Vera, Luis A.; Gantiva, Carlos; Torres, Leidy (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Adaptation of the Alcohol Use Disorders Identification Test (AUDIT) in Colombian university students. Although alcohol consumption is one of the behaviors that generates more negative consequences for public health, there are few validated instruments that allow to measure alcohol consumption in Colombian population. The objective of the present investigation was to adapt the Alcohol Use Disorders Identification Test (AUDIT) in a sample of Colombian university students. The method used was instrumental, because the questionnaire was submitted to the technical adaptation process defined by WHO. It was applied to a sample of 1,557 Colombian university students, selected under a probabilistic procedure. The results showed that the scale (a) has adequate clarity in its language, (b) fits a well-defined two-factor model, (c) has good levels of reliability (internal consistency) and positive correlations between the items. It was concluded that the AUDIT is a tool with sound psychometric properties to be used in Colombian university students. Resumen: El consumo de alcohol es una de las conductas que genera mayores problemáticas para la salud pública, pero son escasos los instrumentos validados que permiten medirlo en población colombiana. El objetivo de la presente investigación fue adaptar el Cuestionario para Identificación de Trastornos Debidos al Consumo de Alcohol (AUDIT) en universitarios colombianos. El método utilizado fue instrumental, dado que el cuestionario fue sometido al proceso técnico de adaptación definido por la OMS. Se aplicó a una muestra de 1.557 universitarios colombianos, seleccionados bajo un procedimiento probabilístico. Los resultados mostraron que la escala (a) posee claridad adecuada en su lenguaje, (b) se ajusta a un modelo de dos factores bien definidos, y (c) posee buenos niveles de fiabilidad (consistencia interna) y correlaciones positivas entre los reactivos. Se concluye que el AUDIT es un instrumento con propiedades psicométricas apropiadas para ser utilizado en universitarios colombianos.